2000
DOI: 10.1046/j.1365-2168.2000.01566.x
|View full text |Cite
|
Sign up to set email alerts
|

Compliance properties of conduits used in vascular reconstruction

Abstract: Compliant polyurethane grafts offer a greater degree of compliance match than either ePTFE or Dacron.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

7
178
0
2

Year Published

2003
2003
2015
2015

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 232 publications
(187 citation statements)
references
References 28 publications
7
178
0
2
Order By: Relevance
“…2 Surgeons have therefore turned to the use of prosthetic materials like polyethylene terephthalate (Dacron), polytetrafluoroethylene, expanded polytetrafluoroethylene, and polyurethane. [2][3][4][5][6][7][8] However, the results obtained with these prosthetic materials prove to be inferior to those obtained with autologous conduits, especially when the blood vessel diameter is Ͻ5 mm. The problems that can arise when these types of materials are used include increased risk of thrombosis and infection, limited durability, lack of compliance both of the graft and around the anastomosis, 9 and failure as a result of restenosis.…”
mentioning
confidence: 99%
“…2 Surgeons have therefore turned to the use of prosthetic materials like polyethylene terephthalate (Dacron), polytetrafluoroethylene, expanded polytetrafluoroethylene, and polyurethane. [2][3][4][5][6][7][8] However, the results obtained with these prosthetic materials prove to be inferior to those obtained with autologous conduits, especially when the blood vessel diameter is Ͻ5 mm. The problems that can arise when these types of materials are used include increased risk of thrombosis and infection, limited durability, lack of compliance both of the graft and around the anastomosis, 9 and failure as a result of restenosis.…”
mentioning
confidence: 99%
“…This reduced patency has been largely attributed to compliance mismatch between the AVG and the native artery to which it is grafted [18,232,233]. Veins are inherently less compliant than arteries [234] and become even less compliant upon abruptly exposed arterialization [235]. It appears as though change in AVG compliance is an important predictor of AVG failure.…”
Section: Changes In Mechanical Properties Of Vein Grafts Due To Artermentioning
confidence: 99%
“…Stiffness increases in abruptly exposed arterialized AVGs and could contribute to reduced clinical performance [234,235] …”
Section: Clinical Performancementioning
confidence: 99%
“…28 This will lead to the formation of intimal hyperplasia (IH). [29][30][31] Thrombosis and IH are different processes; however few studies reported the existence of a relationship between thrombosis and the occurrence of IH, particularly after bypass surgery or angioplasty. 32,33 Thrombin is one of the vital proteins involved in the coagulation pathway: it converts fibrinogen …”
Section: Cardiovascular Graftsmentioning
confidence: 99%